Imprinted Genes Impact Upon Beta Cell Function in the Current (and Potentially Next) Generation - Villanueva-Hayes, Chelsie; Millership, Steven J. (Frontiers in Endocrinology, 2021)
Beta cell failure lies at the centre of the aetiology and pathogenesis of type 2 diabetes and the epigenetic control of the expression of critical beta cell genes appears to play a major role in this decline. One such group of epigenetically-controlled genes, termed ‘imprinted’ genes, are characterised by transgenerational monoallelic expression due to differential allelic DNA methylation and play key functional roles within beta cells. Here, we review the evidence for this functional importance of imprinted genes in beta cells as well as their nutritional regulation by the diet and their altered methylation and/or expression in rodent models of diabetes and in type 2 diabetic islets. We also discuss imprinted genes in the context of the next generation, where dietary overnutrition in the parents can lead to their deregulation in the offspring, alongside beta cell dysfunction and defective glucose handling. Both the modulation of imprinted gene expression and the likelihood of developing type 2 diabetes in adulthood are susceptible to the impact of nutritional status in early life. Imprinted loci, therefore, represent an excellent opportunity with which to assess epigenomic changes in beta cells due to the diet in both the current and next generation.